Urban heat islands advance the timing of reproduction in a social insect. (February 2019) - Chick, Lacy D.; Strickler, Stephanie A.; Perez, Abe; Martin, Ryan A.; Diamond, Sarah E.
Abstract: For many species, the timing of life cycle events is advancing under contemporary global climate change. However, much less is known regarding phenological shifts as a result of other sources of anthropogenic change, such as urban warming. In both cases, progress has been hampered by a focus on phenological traits such as the timing of emergence, rather than the phenology of more directly related fitness traits such as the timing of reproduction. Here we explore how urban heat island effects shape the timing of reproduction in an acorn-dwelling ant. We used a common garden experiment with acorn ants collected from three cities in the eastern United States along a latitudinal gradient and reared long-term in the laboratory under five temperature treatments. This allowed us to quantify the effects of temperature on reproductive phenology across three scales—a biogeographic temperature cline, three urban vs. rural temperature comparisons, and five laboratory rearing temperatures. At our northernmost and southernmost cities (spanning 6° of latitude), we found both urbanization and warmer laboratory rearing temperature significantly advanced reproductive phenology; ants from the lowest latitude city also had earlier reproductive phenology compared with the higher latitude cities. In the field, the differences in urban versus rural acorn ant reproductive phenology translate to approximately one month earlier reproduction in the urban populations. For insects with synchronous mating events, such as ants, shifts in the already short window of time to reproduce could limit mating across environments, potentially leading to reproductive isolation between urban and rural populations. Highlights: Warmer temperatures change the timing of life cycle events. Urban heat island effects increase temperatures in cities compared to rural areas. Urbanization and warmer lab rearing temperatures advanced reproductive phenology. Reproduction advanced approximately one month for ants in urban populations. Shifts in phenology could limit mating across urban and rural populations.